An assessment of the psychometric properties of the Brief Sensation Seeking Scale and its prediction in safety performance in a Portuguese adult sample - Sousa, Cátia (2021)
This study aims to present the psychometric properties of the Brief Sensation Seeking Scale in a Portuguese sample. Three studies were performed: the first study provides psychometric evidence pertaining to its reliability and factor structure, an analysis of the measurement invariance of the BSSS across gender and age, and an examination of the differences scores on the scale regarding gender, age and marital status (n = 526); the second study consists of an assessment of convergent, discriminant and postdictive validity (n = 240); and the third study includes a test-retest of the BSSS (n = 72). A four-factor model yielded the best fit to the data with good reliability and validity. The scale showed non-invariance between genders and between ages, which makes it less generalizable and susceptible to different populations. Convergent validity with the variables risk taking, need for arousal and extraversion, and discriminant validity between neuroticism, agreeableness and conscientiousness, were demonstrated. The scale presents good temporal stability and represent an important tool for psychological assessment of personality and behavior, and as a predictor of safety performance.